Clinical Profile of Primary Headache Patients - Yudawijaya, Agus; Shirley Londo, Auxilia Briliana; Lasma Aritonang, Christina Roseville (Rifa'Institute, 2025)
Introduction: Primary headache is a neurological disorder not caused by structural abnormalities or other medical conditions. It affects people globally and can occur across different ages, genders, and socioeconomic backgrounds. Objective: This study aims to describe the demographic and clinical profile of patients diagnosed with primary headache at the Tanjung Priok Health Center during January–December 2023. Method: A descriptive cross-sectional approach was used. Data were collected through a total sampling technique based on patient medical records. A total of 125 patients met the inclusion criteria. Result and Discussion: The most prevalent diagnosis was tension-type headache, accounting for 74.4% of cases. Most patients were female (61.6%) and aged between 31 and 60 years (51.2%). Housewives represented the largest occupational group (52.8%). Medication was the most frequently used treatment (90.4%). These findings suggest that hormonal, lifestyle, and psychosocial factors may contribute to the higher prevalence among adult women. Conclusion: Tension-type headache was the dominant form of primary headache. Most cases occurred in women aged 31–60 years, predominantly housewives, with medication being the main therapeutic option.